Case Report: Pituitary metastasis as a presenting manifestation of silent gastric cardia adenocarcinoma - Ghezzi, Andrea; Rossi, Jessica; Cavallieri, Francesco; Napoli, Manuela; Pascarella, Rosario; Rizzi, Romana; Russo, Marco; Salomone, Gaetano; Romano, Antonio; Iaccarino, Corrado; Froio, Elisabetta; Serra, Silvia; et al. (Frontiers in Oncology, 2023)
Introduction Pituitary metastases are very rare in cancer patients and often originate from lung or breast tumors. They usually occur in patients with known metastatic disease, but rarely may be the first presentation of the primary tumor. Methods We present the case of a 58 years-old-man who reported a three-month history of polyuria-polydipsia syndrome, generalized asthenia, panhypopituitarism and bitemporal hemianopsia. Brain-MRI showed a voluminous pituitary mass causing posterior sellar enlargement and compression of the surrounding structures including pituitary stalk, optic chiasm, and optic nerves. Results The patient underwent neurosurgical removal of the mass. Histological examination revealed a poorly differentiated adenocarcinoma of uncertain origin. A total body CT scan showed a mass in the left kidney that was subsequently removed. Histological features were consistent with a clear cell carcinoma. However, endoscopic examination of the digestive tract revealed an ulcerating and infiltrating adenocarcinoma of the gastric cardia. Total body PET/CT scan with 18F-FDG confirmed an isolated area of accumulation in the gastric cardia, with no hyperaccumulation at other sites. Conclusion To the best of our knowledge, there are no reports of pituitary metastases from gastric cardia adenocarcinoma. Our patient presented with symptoms of sellar involvement and without evidence of other body metastases. Therefore, sudden onset of diabetes insipidus and visual deterioration should lead to the suspicion of a rapidly growing pituitary mass, which may be the presenting manifestation of a primary extracranial adenocarcinoma. Histological investigation of the pituitary mass can guide the diagnostic workup, which must however be complete.